2003
DOI: 10.1080/00016480310001132
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Tracheal Replacement in Mongrel Dogs

Abstract: The use of alcohol-preserved allografts is a practical method of tracheal transplantation, and the alcohol-preservation technique markedly reduces the immunogenicity of the grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…, ϫ4,800). Chondrocyte membranes and nuclei were frequently observed to be ruptured (3). Density of the mitochondrial matrix (4) was increased, and other intracellular organelles were destroyed (left).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, ϫ4,800). Chondrocyte membranes and nuclei were frequently observed to be ruptured (3). Density of the mitochondrial matrix (4) was increased, and other intracellular organelles were destroyed (left).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that irradiation, preservation in alcohol, and detergent treatment (Triton X-100) could reduce the antigenicity of tracheal grafts. [2][3][4] However, tracheal grafts could not be preserved for a long time using these methods. Additionally, these procedures are complicated.…”
mentioning
confidence: 99%